2012
DOI: 10.1179/1362171811y.0000000082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B on microstructure and hardenability of resistance seam welded HSLA linepipe steel

Abstract: The effects of B on the microstructural and mechanical characteristics of resistance seam welded high strength low alloy linepipe steel were investigated at different regions, such as weld, heat affected zone (HAZ) and base. Because most of the solute B atoms were already precipitated as iron borocarbides and iron borides in as welded steels, the improved hardenability was not observed regardless of the observed regions. The amount of dissolved B precipitates increased with austenitising temperature, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Table 5 Weld nugget diameters and tensile peel strengths of resistance spot welds at I(max). (See Table 2 The embrittlement of welds resulting from the segregation of phosphorous to grain boundaries is reported to be reduced due to the addition of boron [13,15]. EPMA analysis indicated that with an addition of 27 ppm of boron, the phosphorous segregation at the grain boundaries in the fusion zone of Steel-CPB was reduced considerably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 Weld nugget diameters and tensile peel strengths of resistance spot welds at I(max). (See Table 2 The embrittlement of welds resulting from the segregation of phosphorous to grain boundaries is reported to be reduced due to the addition of boron [13,15]. EPMA analysis indicated that with an addition of 27 ppm of boron, the phosphorous segregation at the grain boundaries in the fusion zone of Steel-CPB was reduced considerably.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of boron to phosphorous containing steels is known to improve grain boundary cohesion by reducing phosphorous segregation, thereby reducing embrittlement [12,13]. Boron also improves the hardenability of steels, mainly by retarding the nucleation of polygonal ferrite at austenite grain boundaries [14][15][16]. Babu et al [14] report different weld sizes for two steels with nominally identical compositions, one containing 5 ppm boron by weight and the other 20-40 ppm boron by weight.…”
Section: Introductionmentioning
confidence: 99%
“…Even ferrite islands are still present in the structure. The identified nonmetallic inclusions [39] give hints that interlocking structures were formed. However, the number of inclusions might have been too small (below 10 to 26% [40]) to form acicular ferrite (AF).…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…57,58 The other of great interest is to alter WM composition either through the use of newer filler metals or by metal powder additions in the WM. [59][60][61][62][63] Many of the basic microstructural principles that apply to the HAZ are also valid with respect to the WM. However, an additional important microstructure is acicular ferrite (AF), consisting of fine interlocking grains, which is associated with good toughness.…”
Section: Weld Metalmentioning
confidence: 99%